2017
DOI: 10.1080/14767058.2017.1402876
|View full text |Cite
|
Sign up to set email alerts
|

Association of first-trimester maternal lipid profiles and triglyceride-glucose index with the risk of gestational diabetes mellitus and large for gestational age newborn

Abstract: Based on our findings, TyG index is more robust early predictors of GDM and LGA in Iranian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 27 publications
4
58
1
Order By: Relevance
“…Currently, a single study has assessed the TyG index as a predictor of GDM in Iranian women who attended health centers. Women with TyG index values in the third tertile showed a fivefold risk of developing GDM 9 . Nevertheless, baseline FPG, triglycerides, and BMI at 9 weeks of pregnancy were higher in the Iranian women than those encountered in Latin American women at 13 weeks of pregnancy in our study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, a single study has assessed the TyG index as a predictor of GDM in Iranian women who attended health centers. Women with TyG index values in the third tertile showed a fivefold risk of developing GDM 9 . Nevertheless, baseline FPG, triglycerides, and BMI at 9 weeks of pregnancy were higher in the Iranian women than those encountered in Latin American women at 13 weeks of pregnancy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, impaired glucose tolerance was not determined at enrollment in the Iranian women. Conversely to our sample, Pazhohan et al 9 found a statistical difference in age and BMI between GDM cases and non‐GDM cases, while parity and previous GDM were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations